Answer:
30 divided by 2 = D
Step-by-step explanation:
None
Do the same thing as the attached image.
Multiply the first equation by 2 to then use elimination by adding the 2 equations.
So, 14x-2y=14
+. x+2y=6
Equals 15x=20 so x=20/15=4/3
Plug in to first equation to get y
7(4/3)-y=7
28/3-y=7
28/3-y=21/3
So y=7/3
Plug both x and y into second equation to check
4/3+2(7/3)=
4/3+14/3=18/3=6 it works
So x=4/3, y=7/3
Hope this helps! Have a blessed day!
Answer:
a:c = 35:24
a:c = 20:27
a:c = 35:22
a:c = 28:27
Step-by-step explanation:
a:b = 7:3
Using cross products
3a = 7b
Divide by 7
3a/7 = b
Now we want
8b = 5c
Substitute in 3a/7 for b
8 (3a/7) = 5c
24/7a = 5c
Multiply by 7
24/7a *7 = 5*7c
24a = 35c
Divide by c
24 a/c = 35
Divide by 24
a/c = 35/24
a:c = 35:24
a:b = 4:9
Using cross products
9a = 4b
Divide by 4
9a/4 = b
Now we want
3b = 5c
Substitute in 9a/4 for b
3 (9a/4) = 5c
27/4a = 5c
Multiply by 4
27/4a *4 = 5*4c
27a = 20c
Divide by c
27 a/c = 20
Divide by 27
a/c = 20/27
a:c = 20:27
b:c = 5:11
Using cross products
11b = 5c
Divide by 11
b = 5c/11
Now we want
2a = 7b
Substitute in 5c/11 for b
2a = 7(5c/11)
2a = 35c/11
Multiply by 11
2a*11 = 35c
22a = 35c
Divide by c
22 a/c = 35
Divide by 22
a/c = 35/22
a:c = 35:22
b:c = 14:3
Using cross products
3b = 14c
Divide by 3
b = 14c/3
Now we want
9a = 2b
Substitute in 14c/3 for b
9a = 2(14c/3)
9a = 28c/3
Multiply by 3
9a*3 = 28c
27a = 28c
Divide by c
27 a/c = 28
Divide by 27
a/c = 28/27
a:c = 28:27